2018
DOI: 10.1590/1414-431x20187541
|View full text |Cite
|
Sign up to set email alerts
|

Acute exercise inhibits gastric emptying of liquids in rats: influence of the NO-cGMP pathway

Abstract: We previously found that acute exercise inhibited the gastric emptying of liquid in awake rats by causing an acid-base imbalance. In the present study, we investigated the involvement of the nitric oxide-cyclic guanosine monophosphate (NO-cGMP) pathway, vasoactive intestinal peptide (VIP), and corticotropin-releasing factor (CRF) peptide in this phenomenon. Male rats were divided into exercise or sedentary group and were subjected to a 15-min swim session against a load (2.5 or 5% b.w.). The rate of gastric em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
(69 reference statements)
0
3
0
Order By: Relevance
“…In this sense, we recently reported that acute exercise delays the gastric emptying rate in rats, a phenomenon prevented by bicarbonate treatment. In addition, extracellular acidosis in vitro inhibits cholinergic neurotransmission in the rat gastric fundus by selectively influencing the Gq/11 protein-signaling pathway (22,23). Now, we report for the first time the morphofunctional modifications in the intestinal barrier, such as increased intestinal permeability associated with changes in the transcription of a tight junction (claudin-2) in a physically exhaustive test, which was prevented by AG treatment.…”
Section: Discussionmentioning
confidence: 74%
“…In this sense, we recently reported that acute exercise delays the gastric emptying rate in rats, a phenomenon prevented by bicarbonate treatment. In addition, extracellular acidosis in vitro inhibits cholinergic neurotransmission in the rat gastric fundus by selectively influencing the Gq/11 protein-signaling pathway (22,23). Now, we report for the first time the morphofunctional modifications in the intestinal barrier, such as increased intestinal permeability associated with changes in the transcription of a tight junction (claudin-2) in a physically exhaustive test, which was prevented by AG treatment.…”
Section: Discussionmentioning
confidence: 74%
“…Upon increasing tissue concentrations of ANG II, activation of AT1 and AT2 receptors in the gastric mucosa may contribute to changes in stomach motor activity ( 24 ). Activation of AT1 receptors induces gastric vasoconstriction, thus resulting in deficits in NO production and activity with a direct impact on the GE rate ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is important to study the causes of the abnormal structure, function, quantity, and distribution of ICCs to understand GID diarrhea after TBI. Studies have shown that the nitric oxide-cyclic guanosine monophosphate (NO-cGMP) pathway is associated with gastric emptying in rats (Akm et al, 2018) and that it plays an inhibitory role in the pacing potential of mouse small intestinal ICCs (Kim et al, 2018). In contrast, VIP inhibits the pacemaker activity of ICCs via the NO-cGMP-PKG pathway (Kim et al, 2006).…”
Section: Introductionmentioning
confidence: 99%